2013
DOI: 10.1007/s10633-013-9405-y
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral visual dysfunction in prematurely born children attending mainstream school

Abstract: The prevalence of CVD in these prematurely born children is between 21-47 % (95 % CI), with a pattern similar to "dorsal stream dysfunction". Currently available perceptual tests appear to be unable to identify the specific pattern of problems noted in this group. Many studies have provided evidence of cognitive and intellectual dysfunction in prematurely born children, and it is possible that CVD is a contributor. The CVI inventory is a potential means of identifying and characterising the condition, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 32 publications
3
70
1
Order By: Relevance
“…In addition, with advances in medicine, white matter abnormalities have become less widespread and severe (23), which in turn might have resulted in a concomitant decrease of (severe) CVI. Our finding contrasts assumed visual rehabilitation needs for VP/VLBW children with CVI (16). Although the lack of visual service use might also reflect unmet needs, referrals to visual rehabilitation were not restricted by narrow acceptance criteria.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In addition, with advances in medicine, white matter abnormalities have become less widespread and severe (23), which in turn might have resulted in a concomitant decrease of (severe) CVI. Our finding contrasts assumed visual rehabilitation needs for VP/VLBW children with CVI (16). Although the lack of visual service use might also reflect unmet needs, referrals to visual rehabilitation were not restricted by narrow acceptance criteria.…”
Section: Discussioncontrasting
confidence: 89%
“…CVI-status was specifically accompanied by medium to large sized increases in parent-reported vision-related problems on the CVI Inventory, supporting the concurrent validity of our CVI concept. Other studies using different approaches found similar results in very preterm born children and among children referred to a CVI clinic (16,17). In addition, parent-reported visionrelated problems in VP/VLBW children with CVI remained largely present irrespective of selective and executive attention abilities, indicating that these visual problems exist independent of attention problems of very preterm born children (18).…”
Section: Discussionsupporting
confidence: 57%
“…(3) At the other end of the spectrum, perceptual visual dysfunction with normal or near normal visual acuities and abilities commensurate with mainstream education has also been described in relation to premature birth (Macintyre-Béon et al 2013 ). Such 'minor' degrees of perceptual visual dysfunction may not be uncommon but may be going unrecognised (Williams et al 2011 ).…”
Section: The Concept Of CVI (Cerebral Visual Impairment)mentioning
confidence: 99%
“…More than half of the children (55 %) showed optic nerve atrophy; about two-thirds suffered from epilepsy. The relatively severe nature of the visual features described indicates that children with ostensibly perceptual visual dysfunction alone, that for example, may well be common but often undiagnosed sequel to premature birth (MacIntyre-Béon et al 2013 ), and may be not infrequent in the general population (Williams et al 2011 ), were probably not included in these studies. In two children without associated cognitive developmental disorders, CVI was caused by bilateral occipital cysts and by an occipital tumour, respectively, the latter being removed at the age of 2 years.…”
Section: 2 )mentioning
confidence: 99%
“…Differentiating the effects on vision of CVI and ROP can be difficult except when the retina is obviously disorganised. CVI encompasses a wide range of effects from blindness through to visual neglect and simultanagnosia (inability to process a crowded scene) 33. The latter may not be detected by routine clinical assessment such as visual acuity measurement, requiring specific questions to elicit difficulties in visual perception.…”
Section: Visual Functionsmentioning
confidence: 99%